The discovery of a new species of Brunellia (Brunelliaceae) with ephemeral petals from Llanganates National Park, Ecuador - Orozco, Clara Inés; Pérez, Álvaro J.; Romoleroux, Katya; Aldana, José Murillo (Phytotaxa, 2017)
Brunellia ephemeropetala, a new species discovered in Llanganates National Park, Ecuador is described and illustrated. This species belongs to a group of species that have unifoliate leaves, large fruits and navicular endocarp, in which B. ephemeropetala is distinguished by large and thin stipules, leafy inflorescence and the presence of a petal whorl. For the first time, the presence of petals is recorded in Brunellia, a genus previously considered apetalous.